Suicidality and gambling among young adults in Great Britain: results from a cross-sectional online survey - Wardle, Heather (Lancet Public Health, 2021)
BACKGROUND: Suicide rates in young people have increased in England and Wales since 2010. There are a range of possible explanations for this increase, and problem gambling has been suggested as a potential risk factor. We aimed to examine the association between suicidality (suicidal thoughts and suicide attempts) and problem gambling specifically for young adults in Great Britain, where gambling has become more widely available and normalised in the past two decades. METHODS: We analysed data from the Emerging Adults Gambling Survey: a cross-sectional, online, non-probability sample survey of young adults aged 16–24 years living in Great Britain, who were selected from a YouGov online panel. Participants were eligible if they had not taken part in any other YouGov survey on gambling in the past year. We examined associations between problem gambling (defined as a score of 8 or higher on the Problem Gambling Severity Index [PGSI]) and suicidal thoughts and suicide attempts in the year before survey completion in a series of regression models, with and without adjustment for sociodemographic factors, alcohol use, video gaming, anxiety, loneliness, and impulsivity. FINDINGS: 3549 eligible participants completed the survey between June 25 and Aug 16, 2019. 24 (37·0% [95% CI 25·6–50·2]) of 62 men who had attempted suicide in the past year had survey scores that were indicative of problem gambling, compared with 38 (3·6% [2·6–5·0]) of 1077 men who had not attempted suicide or had suicidal thoughts in the past year. 13 (14·5% [8·5–23·6]) of 85 women who had attempted suicide in the past year had survey scores that were indicative of problem gambling, compared with 25 (2·0% [1·4–3·0]) of 1184 women who had not attempted suicide or had suicidal thoughts in the past year. The adjusted odds ratio for attempted suicide was 9·0 (4·1–19·7) in men with scores that indicated problem gambling and 4·9 (2·0–12·0) in women with scores that indicated problem gambling, compared with participants of the same gender with PGSI scores of 0. INTERPRETATION: Problem gambling appears to be associated with suicide attempts in both young men and young women. This association persisted after adjusting for anxiety, impulsivity, life satisfaction, and other factors, which suggests that other mechanisms, such as the severity and multiplicity of harms experienced, or gambling to cope with life stressors, might underpin this relationship. Young people with problem-gambling behaviours should be considered at risk for suicidality. FUNDING: Wellcome Trust.